Hiatus resolution strategies in a Southern Nigerian English accent - Melefa, Omotosho Moses; Amoniyan, Oluwasegun Matthew; Egwahor, Daniel (Penerbit Universiti Kebangsaan Malaysia, 2024)
Studies on the Nigerian accents of English are yet to provide any empirical account of the handling of hiatus, and little is known about the strategies that Ika speakers of English adopted to resolve it. Therefore, this paper discusses how Educated Ika speakers of English (EISE) handle hiatus and the strategies adopted. A specially prepared text was administered to and read into a tape recorder by 60 EISE from Delta State University, Nigeria, who were selected through a simple random sampling technique to achieve this aim. The recordings were analysed perceptually, acoustically, theoretically, and statistically. The acoustic analysis was done using Praat, version 6.0., while Prince and Smolensky’s Optimality theory (OT) served as the theoretical framework for data analysis. The findings reveal that EISE prohibits hiatus, and the repair strategies adopted by the speakers are consonant epenthesis and vowel elision, respectively. Constraints for the identified strategies are ranked by the participants thus: ONSETWM>> *VV>> INS(C) >>HET-SYLL >> PARSEPF >> DEP-IO>> MAXIO>>IDENT-IO. The study concludes that the handling of hiatus by these participants further provides evidence that Nigerian English accents vary from inner circle accents.